Bridging Psychology and HRM in the Posthuman Era: A Bibliometric Exploration of Emotional Intelligence, Mental Health, and Employee Performance - ., Hamsal; ., Marnis; ., Samsir; Garnasih, Raden Lestari (Journal of Posthumanism, 2025)
This study investigates how psychological theories specifically emotional regulation, motivation, and personality traits enhance Human Resource Management (HRM) strategies, focusing on employee well-being and organizational performance. Employing a bibliometric and systematic review of 440 academic articles, it reveals that integrating psychology into HRM, particularly through High-Performance Work Systems (HPWS), leads to improved employee engagement, job satisfaction, and mental health. Emotional intelligence (EI) emerges as a critical factor, mitigating stress and burnout. Nonetheless, challenges like cultural diversity and resistance to change require context-specific interventions. This research offers a global perspective and practical recommendations to optimize HR practices through psychological principles.